Mitochondrial Dysfunction in Neurodegenerative Diseases: Mechanisms and Corresponding Therapeutic Strategies - Kai Meng; Haocheng Jia; Xiaoqing Hou; Ziming Zhu; Yuguang Lu; Yingying Feng; Jingwen Feng; Yong Xia; Rubin Tan; Fen Cui; Jinxiang Yuan (Biomedicines)
Neurodegenerative disease (ND) refers to the progressive loss and morphological abnormalities of neurons in the central nervous system (CNS) or peripheral nervous system (PNS). Examples of neurodegenerative diseases include Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). Recent studies have shown that mitochondria play a broad role in cell signaling, immune response, and metabolic regulation. For example, mitochondrial dysfunction is closely associated with the onset and progression of a variety of diseases, including ND, cardiovascular diseases, diabetes, and cancer. The dysfunction of energy metabolism, imbalance of mitochondrial dynamics, or abnormal mitophagy can lead to the imbalance of mitochondrial homeostasis, which can induce pathological reactions such as oxidative stress, apoptosis, and inflammation, damage the nervous system, and participate in the occurrence and development of degenerative nervous system diseases such as AD, PD, and ALS. In this paper, the latest research progress of this subject is detailed. The mechanisms of oxidative stress, mitochondrial homeostasis, and mitophagy-mediated ND are reviewed from the perspectives of β-amyloid (Aβ) accumulation, dopamine neuron damage, and superoxide dismutase 1 (SOD1) mutation. Based on the mechanism research, new ideas and methods for the treatment and prevention of ND are proposed.